Some Comments on the Functional Structure of E-Textbooks - Achilov Utkir Isomitdinovich (Researchparks Publishing, 2022)
Creating a textbook on a subject that is a leading component of educational content in the process of globalization. In the process of designing the textbook, not only specialists in the field of narrow subject science, but also specialists in the field of electronic textbook didactics, psychologists and, most importantly, programmers responsible for the final implementation of the project. To facilitate the software, to adapt the textbook and to create individual learning trajectories, the educational material (electronic textbook content) is divided into functional units. A graphically oriented approach to the structure of the learning material is the construction of individual learning trajectories, a person-centered approach to teaching